1968
DOI: 10.1111/j.1532-5415.1968.tb01273.x
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Wave Velocity in the Human Aorta*

Abstract: After introduction of a catheter into the aorta, the pressure wave velocity was measured in 26 subjects whose ages ranged from 9 to 68 years. The first site of registration was approximately 10 cm from the aortic valve, and the second was 50 cm distal to the first. At both sites the time difference was measured between the R‐wave of the electrocardiogram and the foot of the pressure wave (TProx. and TDist.). The time difference T50 (TDist. – TProx.) and the distance between the sites of registration (50 cm) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1968
1968
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Thus in groups in which no patient has a systolic blood pressure above 250 mm, it appears that age has the dominating influence on pulse wave velocity. The exclusion of the 2 patients made the data on systolic blood pressure and pulse pressure comparable with the data on 26 patients in whom we previously measured the pressure wave velocity by means of an intra‐arterial technique and from which exactly the same conclusions (3) were drawn. The conflicting results in the literature on the influence of the systolic blood pressure on the pulse wave velocity therefore can possibly be explained by differences in the blood pressure levels of the groups under study.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Thus in groups in which no patient has a systolic blood pressure above 250 mm, it appears that age has the dominating influence on pulse wave velocity. The exclusion of the 2 patients made the data on systolic blood pressure and pulse pressure comparable with the data on 26 patients in whom we previously measured the pressure wave velocity by means of an intra‐arterial technique and from which exactly the same conclusions (3) were drawn. The conflicting results in the literature on the influence of the systolic blood pressure on the pulse wave velocity therefore can possibly be explained by differences in the blood pressure levels of the groups under study.…”
Section: Discussionmentioning
confidence: 67%
“…We have previously reported (in this issue of the Journal) our results with the determination of the pressure wave velocity in the aorta (3). After the insertion of a catheter the time difference was measured between the R‐wave of the electrocardiogram and the foot of the pressure wave, the pressure wave being first recorded approximately 10 cm distally from the aortic valve, and then (after retracting the catheter) 50 cm distally from the first point of measurement.…”
mentioning
confidence: 78%
“…The pulse wave velocity correlates with age and depends upon the diastolic pressure and the elasticity of the blood vessel (17, 48–51). Hallock (52) found that the aortic pulse wave velocity increased from 4.1 meters/second at age 5 years, to 10.5 meters/second at age 65.…”
Section: Physiologic Changesmentioning
confidence: 99%
“…The pulse wave velocity correlates with age and depends upon the diastolic pressure and the elasticity of the blood vessel (17,(48)(49)(50)(51)…”
Section: Physiologic Changesmentioning
confidence: 99%